Immunostimulatory Activities of CpG-Oligodeoxynucleotides in Teleosts: Toll-Like Receptors 9 and 21 - Lai, Chao-Yang; Yu, Guann-Yi; Luo, Yunping; Xiang, Rong; Chuang, Tsung-Hsien (Frontiers in Immunology, 2019)
Toll-like receptors (TLRs) are pattern-recognition receptors that detect a wide variety of microbial pathogens for the initiation of host defense immunological responses. Thirteen TLRs have been identified in mammals, and teleosts contain 22 mammalian or non-mammalian TLRs. Of these, TLR9 and TLR21 are the cytosine-phosphate-guanosine-oligodeoxynucleotides (CpG-ODNs) recognition TLRs in teleosts. TLR9 is a mammalian TLR expressed in teleost but not in the avian species. TLR21 is a non-mammalian TLR expressed in both teleost and the avian species. Synthetic CpG-ODNs are potent immunostimulants that are being studied for their application against tumors, allergies, and infectious diseases, and as a vaccine adjuvant in humans. The immunostimulatory effects of CpG-ODNs as vaccine adjuvants and their antimicrobial function in domestic animals and teleosts are also being investigated. Most of our current knowledge about the molecular basis for the immunostimulatory activity of CpG-ODNs comes from earlier studies of the interaction between CpG-ODN and TLR9. More recent studies indicate that in addition to TLR9, TLR21 is another receptor for CpG-ODN recognition in teleosts to initiate immune responses. Whether these two receptors have differential functions in mediating the immunostimulatory activity of CpG-ODN in teleost has not been well studied. Nevertheless, the existence of two recognition TLRs suggests that the molecular basis for the immunostimulatory activity of CpG-ODN in teleosts is different and more complex than in mammals. This article reviews the current knowledge of TLR9 and TLR21 activation by CpG-ODNs. The key points that need to be considered for CpG-ODNs as immunostimulants with maximum effectiveness in activation of immune responses in teleosts are discussed. This includes the structure/activity relationship of CpG-ODN activities for TLR9 and TLR21, the structure/functional relationship of these two TLRs, and differential expression levels and tissue distributions for these two TLRs.